CONSTRUÇÃO E VALIDAÇÃO DE UMA MESA DE TENSÃO PARA DETERMINAÇÃO DE ATRIBUTOS FÍSICO-HÍDRICOS DO SOLO - FLORA, Murillo Pereira,; GUIMARÃES JÚNNYOR, Wellingthon da Silva,; RODRIGUES, Gustavo Sanches,; SILVA, Fagner Luiz Rodrigues,; RODRIGUES, Nicolly Queiroz,; DOS SANTOS, Maria Aparecida do Nascimento, (ANAIS DO ENIC, 2023)
-